Neglected Anterior Dislocation of the Knee with Common Peroneal Palsy - Thomas Matthai; Kaushik Bhowmick; P. R. J. V. C. Boopalan; James C. George (Case Reports in Orthopedics)
Knee dislocations usually follow high velocity injuries and are increasingly being treated with immediate reduction and staged repair of the ligaments. Neglected knee dislocations are rare and more difficult to treat with inferior outcomes. We present a rare case of neglected anterior dislocation of the knee treated by surgical arthrodesis.